UPAYA PEMEINTAH DESA DALAM MENYOSIALISASIKAN LAMPIRAN KEPUTUSAN MENTERI NO 8 TAHUN 2017 TENTANG PEMANFAATAN LAHAN PEKARANGAN RUMAH UNTUK MENINGKATKAN KESEJAHTERAAN KELUARGA (Studi di Desa Wamboule Kecamatan Kulisusu Utara Kabupaten Buton Utara) - Adilan, Ervilan; Kasim, Syaifuddin S.; Supiyah, Ratna (Universitas Halu Oleo, 2020)
This study aims to determine the village government's efforts in disseminating the ministerial decision No. 8 of 2017 concerning land use home gardens to improve the welfare of the family and community responses to the socialization of land use homestead in the village of North Kec.Kulisusu Kab.Buton Wamboule North. This study used descriptive qualitative data collection techniques are observation, interview, documentation. Informants of this research consisted of 10 people, which is 3 people as key informants (The Villages) and 7 as an additional informant (Society).These results indicate that the government's lack of socialization village homestead on land use so there are many people who do not understand and do not take advantage of home gardens as productive land, then to continue this program of village government distribute plant seeds every 3 months to the public. People who use land has obtained good results and enough help to meet the needs of everyday family consumption and can reduce and increase household income by selling crops with obtain Rp20,000-Rp25,000 per day. While people who do not take advantage of homestead land caused because not understand the purpose of the land use yard so it is not keen to implement this program. It is also no desire of people's self-due to lazy and do not like eating vegetables.